Interaction analysis of geometric tolerance of multi-axis machine tools based on kinematic Jacobian-Torsor model. (January 2023) - Chen, Kun; Liu, Shun; Tian, Ang; Mo, Wei; Jin, Sun
For the purpose that the multi-axis machine tools can machine workpieces flexibly and accurately, it is important to ensure that each axis of the machine tool can be linked with each other, and the geometric tolerances are within their required range. However, each tolerance is not only related to its own kinematic axis, but also affected by the comprehensive influence of other kinematic axes, which brings great difficulties to the modeling of geometric tolerances. This paper focus on developing a modeling methodology to describe the relationship between the range of machining geometric tolerance and the motional domain of machine tool axe based on an improved Jacobian-Torsor theory. General formulas for the expression of the geometric tolerances are derived. Experiments are carried out on five four-axis machine tools, type CNC-SH50, to verify the effectiveness of the proposed kinematic Jacobian-Torsor model in dealing with the interaction analysis of geometric tolerances.